THE ROLE OF UZBEK NATIONAL VALUES IN URBAN AESTHETICS (American Journal of Research in Humanities and Social Sciences, 2025)
This article explores the integration of Uzbek national values into the aesthetic formation of urban environments. The study analyzes how traditional cultural elements, architectural patterns, and historical heritage influence modern urban planning in Uzbekistan. The research highlights the balance between modernization and cultural continuity, emphasizing how national identity shapes aesthetic perception and the sustainability of urban design.